Individual Characteristic and Reward System Relate to Nurses’ Performance - Kusnanto Kusnanto; Siti Guntarlin; Endah Purnihasti (Universitas Airlangga, 2009)
Introduction : Nurses are one of the most important profession in health care system. Lack of reward systems and different of individual nurse’s characteristic will be contributed to the quality of nursing service given. This study was aimed to explain the correlation between individual characteristic and nurse reward system with nurse’s performance at RSUD Bontang.Methods : This study used cross-sectional design involved 39 respondents, taken by purposive sampling. The independent variable were individual characteristic and nurse reward system and the dependent variable was nurse’s performance. Data were collected by using questionnaires and analyzed using linier regression with level of significance α≤0,05.Results : Results showed that there were significant correlation between nurse’s performance with individual characteristic and reward system.Conclusion : It can be concluded that individual nurse’s characteristic and nurse reward system had correlation between nurse’s performance nursing care quality. Discussion : Individual characteristic factors (sex, age, education, seniority or work period) and nurse’s reward system must be considered to make judgement policy efficiency by human research. Further research must be done for identification factors who related nurse’s performance.